Bilder av en älv : i skärningspunkten mellan energipolitik, kulturarv och feminism - Rönnbäck, Erica (Linköpings universitet, Avdelningen för historia, konstvetenskap och religionsvetenskap, 2022)
This essay explores how an image can be shaped and influenced by several different interests, motives, and schools of thought. The work getting analysed is Till minnet av en älv by Anja Örn. It contains video art, sculptures, and text with a number of different frameworks and references.In the background descriptions made, concepts such as ecofeminism and Anthropocene play a role. The essay also touches upon industrial history and cultural heritage which lifts the interesting question of who's history is being written.It's about how our shared memories are shaped in relationship to the landscape, and who gets represented when these memories are transferred to the next generation.